Effectiveness, safety, and tolerability of bilastine 20 mg vs levocetirizine 5 mg for the treatment of chronic spontaneous urticaria: A double‐blind, parallel group, randomized controlled trial. Issue 6 (27th July 2020) - Podder, Indrashis; Das, Anupam; Ghosh, Shouvik; Biswas, Debalina; Sengupta, Sujata; Chowdhury, Satyendra Nath
Abstract: Chronic spontaneous urticaria (CSU) is a debilitating condition, adversely affecting the patient's quality of life. Bilastine is a recently introduced, non‐sedative H1‐antihistamine for its treatment. We wanted to compare the effectiveness, safety, and tolerability of bilastine 20 mg vs levocetirizine 5 mg in moderate‐to‐severe CSU. We conducted a double‐blind, randomized controlled trial with two groups: bilastine 20 mg (n = 31) and levocetirizine 5 mg (n = 27), once daily for 42 days. We included patients (18‐65 years), with moderate‐to‐severe CSU. UAS7, VAS, and DLQI were used to assess severity of urticaria, global urticaria‐induced discomfort and quality of life, respectively. DLQI was assessed at baseline (D0) and end‐of‐treatment (D42), while UAS7 and VAS were noted at baseline and all follow‐up visits. Assessment of UAS7 alteration was our primary objective, while changes in DLQI and VAS were the secondary outcomes. Safety was assessed by recording drug‐related adverse events, biochemical investigations, and electrocardiogram, along with tolerability and compliance. Both drugs significantly improved UAS7, DLQI, and VAS at end‐of‐treatment (D42) compared with baseline (intra‐group). At the end‐of‐treatment, all parameters showed greater improvement with bilastine, but only UAS7 reduction was significant (bilastine > levocetirizine, P = .03). In both the groups, UAS7 and VAS improved significantly D14 onwards, and was maintained throughout the study. Sedation was significantly less with bilastine ( P = .04), while neither drug showed any serious adverse‐effect. Tolerability of both drugs was similar. Therefore, bilastine was found to be a more effective and less‐sedative novel therapy for CSU compared to levocetirizine, with similar effect on quality of life.